2016
DOI: 10.4103/2303-9027.175884
|View full text |Cite
|
Sign up to set email alerts
|

The utility of endobronchial ultrasound-transbronchial needle aspiration in lymphoma

Abstract: Background and Objectives:Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure that has a well-established role in the diagnosis and staging of lung cancer. This technology is also widely used for the diagnosis of mediastinal masses and cysts as well as other inflammatory disorders such as sarcoidosis. However, the utility of this procedure in the diagnosis and subclassification of lymphoproliferative disorders (LPDs) is not clear. We performed a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…The quality of CB samples are highly promising especially for ALK, ROS1 and PD-L1 typing, when bigger samples are needed. A complication rate observed in our study was comparable with the standard EBUS-TBNA [1,2,[6][7][8].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The quality of CB samples are highly promising especially for ALK, ROS1 and PD-L1 typing, when bigger samples are needed. A complication rate observed in our study was comparable with the standard EBUS-TBNA [1,2,[6][7][8].…”
Section: Discussionsupporting
confidence: 62%
“…EBUS-TBNA is also successfully performed for diagnostic purposes in patients with paratracheal and peribronchial tumours [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…14 There were studies show that EBUS-TBNA could be useful in diagnosing lymphoma with sensitivity arrange from 76% to 90.9%, 4,15 however, recent research reported that reactive LN diagnosed by EBUS-TBNA was confirmed as lymphoma by thoractomy. 16 More biopsy specimens, flow cytometry and immunohistology could help raise diagnostic yield of EBUS-TBNA for lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Less is known, however, about the utility of EBUS-TBNA for diagnosing non-specific intrathoracic inflammatory lymphadenopathy. Pathology and microbiology play distinct roles in diagnosing non-specific intrathoracic lymphadenitis.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of EBUS is principally guiding TBNA (11)(12)(13)(14)(15). Some investigators used EBUS as a tool for detecting pulmonary vascular abnormalities, including the pulmonary thromboembolism and non-thromboembolic pulmonary vascular diseases.…”
Section: Discussionmentioning
confidence: 99%